THE DETERMINANTS OF FDI IN RETAIL INDUSTRIES IN CHINA-THE CASE STUDIES OF CARREFOUR AND TESCO - LIN, CHING-HUI (2008)
This study examines the determinants of Foreign Direct Investment (FDI) in retail industries in China by using case studies of Carrefour and Tesco, and the purpose of this research is to utilise the limited successful leading retailers in China as case studies, Carrefour and Tesco, and other academic studies have been conducted about entry determinants in China's retail sector to find out the key determinants and entry strategies of foreign retailing firms. Furthermore, the motivation of this research is to figure out the most significant determinants for foreign retailers entering successfully in China by applying the most crucial factors and entry mode strategy from this research. Firstly, this research considers three main theories, including the eclectic paradigm theory, the transaction cost theory, and internationalisation theory to analyse and generalise FDI movements and activities of foreign firms worldwide and apply theories to the Chinese market. Additionally, in order to examine and assist the explanation and application of these theories, case studies of Tesco and Carrefour will be utilised as successful models in China's retail industry by collecting primary and secondary data from academic and official journals, corporate reports, financial statements, and other publications. Furthermore, a semi in-depth interview with open-ended questions with a top manager from Tesco China (Hymall) is conducted to find out specific information about successful MNE entry into China and to generalise to most significant determinants of FDI in China. Moreover, case studies of Carrefour and Tesco are further compared with other cases in China from other academic resources to provide the most effective and important FDI determinants in retail sector. This dissertation aim to offer a new perspective of the most crucial FDI determinants used retailing in China, benefiting future research with possible new findings concerning the effective considerations of an entry strategy and entry mode choice into China to foster corporate expansion in this prosperous but complex country.